An organizational learning approach to process innovations the extent and scope of diffusion and adoption in management accounting systems - Seleshi Sisaye, 1951-; Birnberg, Jacob G. (Emerald, 2012)
This book discusses the organizational processes and structural barriers to the diffusion and adoptions of innovations. In this chapter, we address the question of "why innovations fail?"; addresses the organizational learning strategies of adoption and diffusion of process innovation approaches; presents the theoretical framework of organizational learning and process innovations; covers the four typologies of innovations in detail and research questions relating to these four typologies; compares mechanistic and organic innovations, and organizational development (OD) and organizational transformation (OT) innovations; elaborates the organizational learning framework by incorporating the two stages in sociological theories of process innovations: adoption and diffusion.
Keywords: Business & Economics -- Organizational Behavior.; Business & Economics -- Organizational Development*.; Organizational theory & behaviour.; Sociology.; Accounting.; Managerial accounting.; elektronické knihy; electronic books